2023
DOI: 10.1371/journal.pone.0280014
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of life in adults with Down syndrome: A mixed methods systematic review

Abstract: Background As the life expectancy of adults (aged ≥ 18 years) with Down syndrome increases for a plethora of reasons including recognition of rights, access, and technological and medical advances, there is a need to collate evidence about their quality of life. Objective Using Schalock and Verdugo’s multidimensional quality of life assessment model, this systematic review aimed to identify, synthesise and integrate the quantitative and qualitative evidence on quality of life in adults with Down syndrome via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 127 publications
0
5
0
1
Order By: Relevance
“…Furthermore, supporting the families of individuals with DS is an integral part of this long-term care approach. This support encompasses counseling services, providing educational resources about DS, and facilitating support groups where families can share experiences (Ijezie et al, 2023). As individuals with DS transition into adulthood, the focus shifts to maintaining health and fostering independence.…”
Section: Healthcare Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, supporting the families of individuals with DS is an integral part of this long-term care approach. This support encompasses counseling services, providing educational resources about DS, and facilitating support groups where families can share experiences (Ijezie et al, 2023). As individuals with DS transition into adulthood, the focus shifts to maintaining health and fostering independence.…”
Section: Healthcare Approachesmentioning
confidence: 99%
“…There are instances of students with DS achieving significant milestones, excelling in certain subjects, or even participating in mainstream extracurricular activities. These successes highlight the potential of these individuals when given the appropriate support and opportunities (Daunhauer et al, 2014;Ijezie et al, 2023). However, the journey is not without its challenges.…”
Section: Educational Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…La principal causa de DI congénita es el Síndrome de Down (en adelante SD), también conocido como trisonomía 21 debido a que dicha condición es resultado de la presencia de un cromosoma 21 extra, o parte de él (Ijezie et al, 2023). Su incidencia a nivel mundial es de 3,3 por cada 10.000 nacimientos (Antonarakis et al, 2020) y aunque no existen estudios pormenorizados sobre la tasa de incidencia en Chile, Nazer y Cifuentes, (2011), calculan una incidencia en Chile de 2,47 por cada 1.000 niños nacidos, lo que constituye un aumento de más del doble de la tasa reportada en 1972 y correspondería a la tasa de incidencia más alta de Latinoamérica (Nazer & Cifuentes, 2011).…”
Section: Introductionunclassified
“…A systematic review aimed to identify the evidence on QoL in adults with DS; 39 studies were included, with only 7 (17.94%) reported that adults with DS have a good QoL centered around self-determination and interpersonal relations. Most wanted to improve in their independence, relationships, participation in the community, and in the exercise of their human rights (Ijezie et al, 2023).…”
Section: Introductionmentioning
confidence: 99%